Estimates of inpatient admission rates and associated costs for infants before and after China's universal two-child policy - Menghan Shen; Xiaoxia Liang; Yushan Wu; Shixin Fang (BMC, 2022)
Abstract Background China implemented a universal two-child policy in 2015. It is important to understand infants' medical utilization in the context of this policy to inform health policies and resource allocation. Methods This study utilized a 20% random sample of administrative data from China's Urban and Rural Basic Medical Insurance (URBMI) in one of the largest southern Chinese cities from January 2015 to June 2018. Ordinary least squares models were used to estimate changes in inpatient admission rates and costs for infants between 0 and 6 months old after the implementation of China's universal two-child policy. Results The overall inpatient admission rate was 27.2% in 2015 and 31.3% in 2017. Compared with 2015, there was an increase in inpatient admission rates for infants 1 month old or younger (coef = 0.038, 95% CI = 0.029 to 0.047, p < .001) and infants 6 months old or younger (coef = 0.041, 95% CI = 0.030 to 0.052, p < .001) in 2017. The increase was larger for male infants than for female ones. The average inpatient admission cost was 8412.3 RMB ($1320.61) (SD = 15,088.2). There was no increase in inpatient admission costs overall. The average length of hospital stay was 7.3 days, the probability of going to a tertiary hospital was 76.2%, and the share of out-of-pocket costs was 53.0% for all diseases. Conclusion After the implementation of the universal two-child policy in China, there was a significant increase in inpatient admission rates, especially for male infants. The overall associated costs did not change, but the increase in admission rates caused additional economic burdens for families and for social health insurance. Understanding the healthcare utilization of infants in the universal two-child period can provide insight for healthcare resource allocation in a time of dramatic changes in population policy.